Avaliação morfodinâmica e fragilidade ambiental da paisagem no sistema hidrográfico do rio Arauá/SE - Santana, Bruna Leidiane Pereira (2019)
The spatial organization of environmental systems such as river basins results from biophysical and anthropogenic interactions that energize the flow of energy and matter. The different properties inherent to these systems define their fragility and environmental potential. Considering the importance of the theme to highlight the relationship between society and nature, the objective of this study was to evaluate the environmental conditions of the hydrographic system of the Arauá river, with emphasis on the fragilities of the landscape components in relation to land use and occupation. The theoretical-methodological contribution is based on the systemic approach with emphasis on the contributions of Tricart (1977), Ross (1994) and Crepani et al. (1996, 2001). This analysis made possible the compartmentalization of the hydrographic system of the river Arauá in the landscape units of the Tabuleiro do Rio Real and the Coastal Board. The Rio Real Board consists of the subunit of Landscape Pediplanada Surface, subunit of Landscape Dissected in Hills and Spikes and subunit of Landscape Residual Surface with conditioned morphodynamic characteristics, mainly by slope and soils. As for environmental fragility, the classes of low and very strong potential instability predominate and the middle and low classes for emergent instability predominate. In the Coastal Tray, the subunit of Landscape Subhorizontal Degraded Landscape and Subunit of Landscape Dissected in Verts presented morphodynamic performance enhanced by slope and current land use and occupation. In the potential fragility prevailed the average and very strong and in the emergent fragility the medium and strong. Morphodynamic performance in the subunits is signaled by the presence of erosive features such as grooves, terracetes and occasional mass movements, and the instability evidenced in the system has negative repercussions on water resources.